Input-Support-Output Model Evaluation Using Clustering Analysis on Indonesia High School Dataset - Wijayanto, Feri (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
Input-output model has been widely used in many research areas even in educational research. A previous research has proposed an adjusted input-support-output model to evaluate the quality of education development performance in Indonesia. Even though the previous research has found that the proposed model could explain 88% relation of input, support and output on each province when it was implemented on elementary school dataset, it is important to implement the model in other education level dataset to verify its performance. In this research, clustering analysis was used to cluster each group of the datasets of junior high school and senior high school prior to be mapped and simulated using the model. The results of the analysis of the model performance showed a decrease to 60.6% and 57.58% when it is implemented to junior high school and senior high school datasets respectively.